Climate change and thermal comfort in Southern Europe housing: A case study from Lisbon. (October 2015) - Barbosa, Ricardo; Vicente, Romeu; Santos, Rui
Abstract: The world has been experiencing a significant increase in daily average temperatures per decade and climate change scenarios are projecting high probability of more frequent heat waves. In vulnerable regions, like Southern Europe, where most of the residential buildings still rely on natural ventilation for cooling, impact on thermal comfort can be significant in terms of health, well-being and also energy consumption. The question is particularly important for the existing building stock, which was not designed considering the projected future climate conditions and is prone to be subjected to interventions with the purpose of improving thermal performance. The study presents a vulnerability framework and methodology for the assessment of thermal comfort in existing dwellings in the context of climate change. Results relating to a 1960s typical building case study in Lisbon, Portugal, suggest that specific dwelling characteristics, such as orientation, and occupancy profiles are relevant when assessing vulnerability, suggesting significant differences, of up to 91% in discomfort hours on an annual basis. Furthermore, increased insulation seems to be effective in decreasing discomfort, as the best results (48% in discomfort hours decrease) stem from a context of external insulation for a heatwave situation. The methodology can be useful for assessing vulnerability in existing dwellings and its specific conditions. It can also contribute to understanding the effect of energy retrofitting measures in future climate conditions, assisting energy efficiency policies and decision-making regarding retrofit interventions. Highlights: We develop an assessment methodology for relative vulnerability of thermal comfort. We examine changes on both physical characteristics and occupancy of dwellings. We compare results using analytical and adaptive models of thermal comfort. Insulation measures and optimal ventilation can significantly decrease vulnerability.